2018
DOI: 10.1159/000492461
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Echinococcosis Mimicking a Hepatic Neoplasm with Lymph Node Metastasis: A Case Report

Abstract: A 37-year-old man had an asymptomatic 17-mm mass in the liver by health check with ultrasonography. Five years later, he was referred to our hospital because the mass was slightly enlarged with a peripancreatic lymph node. We performed endoscopic ultrasonography fine-needle aspiration (EUS-FNA) to evaluate a lymph node, but it showed amorphous eosinophilic material and eosinophilic infiltrate in necrotic tissue of toothpaste-like white specimen. However, we diagnosed as potentially malignant liver mass with ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…Our data once more illustrate the difficulty in the diagnosis and therapy of hepatic AE. Due to a resemblance of the radiologic features in liver imaging between cholangiocellular carcinoma and AE, misdiagnosis has been reported earlier as a pitfall for this disease [2,10,23,24]. In our study group, the initial indication for major liver resection was suspected intrahepatic cholangiocellular carcinoma in 2 out of 12AE patients.…”
Section: Discussionmentioning
confidence: 72%
“…Our data once more illustrate the difficulty in the diagnosis and therapy of hepatic AE. Due to a resemblance of the radiologic features in liver imaging between cholangiocellular carcinoma and AE, misdiagnosis has been reported earlier as a pitfall for this disease [2,10,23,24]. In our study group, the initial indication for major liver resection was suspected intrahepatic cholangiocellular carcinoma in 2 out of 12AE patients.…”
Section: Discussionmentioning
confidence: 72%
“…"Hydatid cells" or germinal cells are transferred to regional lymph nodes through lymphatic reflux (3). Suspicious metastasis of peripancreatic lymph node in hepatic alveolar echinococcosis was already reported (8).…”
Section: Discussionmentioning
confidence: 99%
“…In 2009, Klaus et al [24] con rmed for the rst time that a patient with AE had regional lymph node involvement. Subsequently, some cases were gradually reported, but all lacked data regarding the incidence and long-term follow-up conclusions [7,8,12,13,25] (Table 2). In 2018, a retrospective analysis [26] of 46 patients in this center found that 7 patients had AE lymph node involvement and proposed that lymph node involvement was not associated with recurrent disease.…”
Section: Discussionmentioning
confidence: 99%
“…If lymph node metastasis is suspected, and puncture should be performed cautiously. EUS-FNA is a good diagnostic tool, but it should be used when the diagnosis is unclear and the patient is from a nonendemic area [8,25]. Pathological diagnosis is the gold standard.…”
Section: Discussionmentioning
confidence: 99%